2022
DOI: 10.1155/2022/9009214
|View full text |Cite|
|
Sign up to set email alerts
|

Adsorption of Crystal Violet Dye from Aqueous Solution using Industrial Pepper Seed Spent: Equilibrium, Thermodynamic, and Kinetic Studies

Abstract: The economic viability of adsorbing crystal violet (CV) using pepper seed spent (PSS) as a biosorbent in an aqueous solution has been studied. A parametrical investigation was conducted considering parameters like initial concentration of dye, time of contact, pH value, and temperature variation. The analysis of experimental data obtained was carried out by evaluating with the isotherms of Freundlich, Sips, Tempkin, Jovanovic, Brouers–Sotolongo, Toth, Vieth–Sladek, Radke–Prausnitz, Langmuir, and Redlich–Peters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%